Exploring the Intersection of Feminist and Psychoanalytic Theory in the Confessional Poetry of Anita Nair and Kamala Das - Sadia Intekhab (East Asian Journal of Multidisciplinary Research, 2023)
The genre of confessional poetry is defined by the poet's personal and frequently extremely emotional experiences. It first appeared in the middle of the 20th century and is characterised by a personal tone and the first-person point of view. This paper shall examine the confessional elements in the poetry of two prominent Indian poets, Anita Nair and Kamala Das, through a feminist and psychoanalytic perspective. In order to examine themes of love, relationships, and identity in their poetry, Nair and Das use personal experiences, emotions, and thoughts in their poems. The paper will examine the intricate power relationships between men and women underlying Nair and Das' poetry. The paper will emphasise the complex intersection of gender, power, and personal experience that underlies Anita Nair's and Kamala Das's poetry through an analysis of the confessional elements in their works.